(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Statement of the problem: Tooth preparation with horizontal finish line requires removal of reasonable amount of tooth structure at the cervical area which affects the remaining tooth structure at this area. Therefore, more conservative preparation design such as biologically oriented preparation technique (BOPT) might be needed to save tooth structure at the cervical area. The Purpose: To Evaluate the effect of Conventional preparation design (horizontal), and Biologically Oriented Preparation Technique (BOPT), on Marginal adaptation, fracture and gingival inflammation score of the translucent zirconia crown in dental esthetic zone. Methodology:, 44 monolithic translucent zirconia single crowns were fabricated inn dental esthetic zone . The patients were separated randomly into two groups. Group1: (horizontal preparation design) Group2: BOPT. After final cementation. The Modified United States Public Health Service (MUSPH) criteria for restoration clinical evaluations were used to assess marginal adaption. Gingival inflammation was assessed using gingival inflammation index. Evaluation of the restoration was at intervals of three, six, nine, and twelve months. Results: Comparison between two groups at different intervals regarding marginal adaptation, fracture and gingival inflammation score revealed statistically insignificant difference. Conclusions: Within limitations of the present one year follow up randomized clinical trial, the following conclusions could be drawn: 1.The conventional and BOPT preparation designs both clinically accepted to provide successful dental restoration The lower gingival inflammation score of the restored teeth with the conventional preparation design compared to that of the BOPT, may not be conclusive as regard the study time frame, indicating that increasing the follow-up period might alter the present finding. Clinical implications: Beyond of all the prosthodontic preparation techniques, knowledge of B.O.P.T. (Biological Oriented Preparation Technique) allows us to achieve predictable and consistent results in terms of periodontal health and gingiva architecture surrounding ceramic restoration. Nevertheless, long term studies are necessary to ensure the benefits of this techniques.